Early enteral nutrition administration and time to achieve resting energy expenditure in critically ill children - Yulman, Annisa Rahmania; Pudjiadi, Antonius Hocky; Tridjaja, Bambang; Kadim, Muzal; Prawitasari, Titis (Paediatrica Indonesiana, 2025)
Background Malnutrition in critically ill children remains a significant concern, as a standardized nutritional support protocol has yet to be developed. Resting energy expenditure (REE) is recommended as a parameter for determining the fulfillment of energy needs in critically ill children, which should ideally be achieved within 72 hours. To achieve these energy needs, enteral nutrition (EN) is believed to have a lower mortality rate and a shorter length of stay compared to parenteral nutrition (PN). Objective  To evaluate the factors associated with delayed EN initiation and late achievement of REE.  Methods Data consisting of age, sex, nutritional status, timing of EN initiation, time required to achieve REE targets, PELOD-2 score, use of ventilators, duration of ventilation, hemodynamic status, use of inotropes and inotropic score, use of sedation, gastrointestinal symptoms, procedures performed during treatment, and technical issues were collected retrospectively from medical records from 2017 – 2018 in the Pediatric Intensive Care Unit (PICU) at Dr. Cipto Mangunkusumo Hospital. The REE was calculated using Schofield formula based on age and sex. These data were used to compare the proportion of the subjects receiving early EN (<48 hours) and delayed EN (>48 hours) and those who achieved REE <72 hours and delayed REE (>72 hours). Multivariate analysis was performed to determine which factors affecting late EN initiation and delayed REE achievement using logistic regression analysis. Results Of 203 subjects, 63.1% received early EN and 67.5% achieved REE at ≤72 hours. Delayed EN was associated with post-abdominal surgery (OR 10.89; 95%CI 4.31 to 27.50; P<0.001), ventilator use (OR 4.60; 95%CI 1.78 to 11.90; P=0.004), inotrope use (OR 4.18; 95%CI 1.56 to 11.17; P=0.002), gastrointestinal symptoms (OR 3.41; 95%CI 1.59 to 7.29; P=0.002), and abnormal nutritional status (OR 2.49; 95%CI 1.09 to 5.72; P=0.031). The REE >72 hours was associated with late EN (OR 20.62; 95%CI 6.48 to 65.65; P<0.001), enteral intolerance after receiving EN (OR 14.77; 95%CI 4.40 to 49.6; P<0.001), and PELOD-2 score ≥7 (OR 3.98; 95%CI 1.01 to 15.66; P=0.048). Conclusion The prevalence of EN and REE within 72 hours in the PICU is quite encouraging. Factors contributing to delayed EN administration include post-abdominal surgery, ventilator use, inotrope use, gastrointestinal symptoms, and abnormal nutritional status.  Delayed EN >48 hours, enteral intolerance after receiving EN, and PELOD-2 score >7 were the factors contributing to delayed REE achievement. However, these delays can be reduced by developing a comprehensive enteral feeding protocol. The factors influencing delayed EN and late REE achievement are an important basis for designing enteral feeding protocols to improve the clinical outcomes of critically ill children in the PICU.